Effects of heat stress on risk perceptions and risk taking. (July 2017) - Chang, Chu-Hsiang; Bernard, Thomas E.; Logan, Jennifer
Abstract: Exposure to extreme heat at work is a serious occupational hazard, as exposure can result in heat-related illnesses, and it has been linked to increased risk of accidents and injuries. The current study aimed to examine whether heat exposure is related to changes in individuals' psychological process of risk evaluation, and whether acclimatization can mitigate the effect of heat exposure. A study with quasi-experiment research design was used to compare participants' risk perceptions and risk-taking behaviors at baseline, initial exposure to heat, and exposure after acclimatization across male participants who were exposed to heat (N = 6), and males (N = 5) and females (N = 6) who were in the control group who were exposed to ambient temperature. Results show that participants perceived the same risky behaviors to be less risky ( p = 0.003) and demonstrated increased risk-taking behaviors ( p = 0.001) after initial heat exposure. While their risk perceptions returned to baseline level after acclimatization, their risk-taking behaviors remained heightened ( p = 0.031). Participants who were not exposed to heat showed no significant fluctuation in their risk perceptions and risk-taking. Our findings support that risk-related processes may explain the effects of heat exposure on increased accidents and injuries beyond its direct impact on heat-related illnesses. Highlights: Little is known about the psychological effects of heat exposure. Heat exposure is related to lower risk perceptions prior to acclimatization. Heat exposure is related to increased risk-taking behaviors. Acclimatization can mitigate the effect of heat exposure on risk-related processes.